Beyond sovereignty: overcoming modern nominalistic cryptotheology. Issue 3 (2nd July 2016) - Bielik-Robson, Agata
Abstract : Although my essay is devoted mostly to Schmitt's theology of sovereignty as the ultimate theory of power, reflecting the hidden 'metaphysical image' of modernity, it also wants to explore a possibility of venturing beyond the theology of power into an alternative theology of promise. By sketching this possible exodus out of the modern power fixation, I first analyse Schmitt's claim about the persistence of political theology, which provides a rationale for modern political practice, and confront it with the critique formulated by Hans Blumenberg in The Legitimacy of the Modern Age (Abbr: LM). But then I try to paint a broader picture of modern cryptotheologies ; by expanding Blumenberg's critique, I show how it paves the way for an alternative pursuit of political theology which seeks to get 'beyond sovereignty.' For Blumenberg, this quest means mostly the attempt to 'overcome Gnosticism, ' which in my paraphrasing indicates 'overcoming of the nominalistic cryptotheology.' In order to secure a proper exorcism of the Gnostic-nominalistic spectre, I want to go back to the sources of a truly alternative, messianic vision which actively opposes the logic of sovereign power with the logic of a yet unrevealed promise. This different theology of the 'hidden God, ' developed mostly by Walter Benjamin and Gershom Scholem, replaces the 'mystery of power' with the 'mystery of promise' which gets us 'beyond sovereignty' for good – which also coincides with the promise of the true historical novum lying at the origin of modernity.